Factor associated with farmers' adaptation practices to weather variability in rice-based farming system in Myinmu township, Sagaing Region, Myanmar - Khaing, Kay Thi (The Journal of Public Affairs and Development, 2017)
Due to its dependence on agro-climate condition, the rice-based farming system in Myyinmu Township in Central Dry Zone (CDZ). Myanmar is one of the sectors that is vulnerable to weather variability. This study aimed to analyze the association of adaptation practices on production and income of rice farmers in Myinmu Township. One hundred fifty farmers were surveyed and key informant interviews were conducted to gather primary data. Results revealed that most farmers received agricultural and weather information from fellow farmers, extension and agents from the Department of Agriculture, attendance to group meetings, and mass media channels such as radio and television. Adaptation practices were categorized into changing cultivated varieties and crops, changing farming systems, conserving rain water, improving irrigation systems, and engaging in non-farm activities.